Safety and efficacy of transvenous lead extraction of very old leads. (30th November 2020) - Pecha, Simon; Ziegelhoeffer, Tibor; Yildirim, Yalin; Choi, Yeong-Hoon; Willems, Stephan; Reichenspurner, Hermann; Burger, Heiko; Hakmi, Samer
Abstract: OBJECTIVES: Transvenous lead extraction using mechanical rotational- or laser sheaths is an established procedure. Lead dwell time has been recognized as a risk factor for extraction failure and procedure-related complications. We therefore investigated the safety and efficacy of transvenous extraction of leads with an implant duration of more than 10 years. METHODS: Between January 2013 and March 2017, a total of 403 patients underwent lead extraction in 2 high-volume lead extraction centres. One hundred and fifty-four patients with extraction of at least 1 lead aged over 10 years were included in this analysis. Laser lead extraction was the primary extraction method, with additional use of mechanical rotational sheaths or femoral snares, if necessary. All procedural- and patient-based data were collected into a database and retrospectively analysed. RESULTS: Mean patient's age was 65.8 ± 15.8 years, 68.2% were male. Three hundred and sixty-two leads had to be extracted. The mean lead dwell time of treated leads was 14.0 ± 6.1 years. Complete procedural success was achieved in 91.6% of cases, while clinical success was achieved in 96.8%. Failure of extraction occurred in 3.2%. Leads that could not be completely removed had a significantly longer lead dwell time (18.2 vs 13.2 years; P = 0.016). Additional mechanical rotational sheaths or femoral snares were used in 26 (16.9%) patients. Overall complication rate was 4.6%, including 5 (3.3%) major and 2 (1.3%) minor complications. There was no procedure-related mortality. CONCLUSIONS: Transvenous lead extraction in leads aged over 10 years is safe and effective when performed in specialized centres and with use of multiple tools and techniques. Leads that could not be completely extracted had a statistically significant longer lead dwell time. Abstract : The number of cardiac implantable electronic devices has been rising in recent years due to an ageing population and expansions in implantable cardioverter defibrillator (ICD)- and cardiac resynchronization therapy (CRT) indications.